Synthesis of nanocrystalline metal molybdates using cyclic microwave radiation - A. Phuruangrat (2018)
Nanocrystalline compounds MMoO4 (M = Ca, Sr and Ba) were synthesized in propylene glycol using cyclic microwave radiation. XRD, TEM, SAED and EDX analyses revealed the presence of nanocrystallites of the phases containing the corresponding alkaline earth metals, Mo and O. The calculated lattice parameters and the crystallite sizes both increased with the increase in the atomic masses and the ionic radii of the divalent metals. Six different vibrations were detected using Raman spectroscopy, and very strong Mo-O stretching mode of [MoO4]2- tetrahedrons was observed using FTIR.